Less than two versus greater than two hour invasive strategy in non-ST elevation myocardial infarction: a meta-analysis of randomized controlled trials. (2nd January 2018) - Velagapudi, Poonam; Turagam, Mohit; Kolte, Dhaval; Khera, Sahil; Parikh, Parag; Hyder, Omar; Aronow, Herbert; Abbott, J. Dawn
ABSTRACT: Background : Optimal timing for an invasive strategy in non-ST elevation myocardial infarction (NSTEMI) is unclear. Whether clinical outcomes are improved with a less than two (LT2) compared with greater than two hour (GT2) invasive strategy remains to be determined. We performed a meta-analysis of randomized controlled trials (RCTs) comparing LT2 vs GT2 for NSTEMI. Methods : A comprehensive literature search for RCTs comparing LT2 vs. GT2 in NSTEMI patients was performed. Three eligible studies consisting of 1, 075 patients (LT2: 537, GT2: 538) with NSTEMI were identified. Follow-up ranged from 1 to 12 months. Results : Time from randomization to sheath insertion ranged from 0.5–2.2 and 14.0–85.0 hours in the LT2 and GT2 groups. More percutaneous coronary interventions and fewer coronary artery bypass grafting were performed in the LT2 vs. GT2 group. There was no significant difference in all-cause mortality, myocardial infarction (MI), and major bleeding between the two groups. LT2 was numerically, but not statistically superior to GT2 at preventing recurrent ischemia/urgent revascularization/refractory ischemia. Conclusion : Our meta-analysis found no significant difference in outcomes between less than two versus greater than two hours invasive strategy for NSTEMI. The differences observed in the mode of revascularization according to timing of catheterization deserve further study.